Study of phospholipases in Trypanosoma brucei brucei - (:unkn) unknown (My University, 2021)
African trypanosomiasis is a vector parasitic disease which affects many mammals in Africa. Among them, we found Men and livestock. One of the symptoms of this affection in animals is anemia. Unfortunately, we do not know the underlying mechanisms of this anemia. Some proteins, such as phospholipases, could play a key role in the physiopathology. Only three of them have been described. The research team I belonged during my pHD describe the different parasitic phospholipases and determine their function. Since phospholipase activity is greater in more virulent parasites, the notion of redundancy in phospholipase activity remains essential. Using in silico analyzes, I was able to start describing some proteins. Then, I expressed some of them in order to study their activity. Functional and molecular analyzes allowed me to study their function in the parasite and to broaden the field of phospholipase activity in Trypanosoma brucei brucei.
Keywords: African Research